Identification and expression profiling of microRNAs in leaf tissues of Foeniculum vulgare Mill. under salinity stress - Luis Alberto Bravo-Vázquez; Mariana García-Ortega; Sara Medina-Feria; Aashish Srivastava; Sujay Paul (Plant Signaling & Behavior)
Foeniculum vulgare Mill. commonly known as fennel, is a globally recognized aromatic medicinal plant and culinary herb with widespread popularity due to its antimicrobial, antioxidant, carminative, and diuretic properties, among others. Although the phenotypic effects of salinity stress have been previously explored in fennel, the molecular mechanisms underlying responses to elevated salinity in this plant remain elusive. MicroRNAs (miRNAs) are tiny, endogenous, and extensively conserved non-coding RNAs (ncRNAs) typically ranging from 20 to 24 nucleotides (nt) in length that play a major role in a myriad of biological functions. In fact, a number of miRNAs have been extensively associated with responses to abiotic stress in plants. Consequently, employing computational methodologies and rigorous filtering criteria, 40 putative miRNAs belonging to 25 different families were characterized from fennel in this study. Subsequently, employing the psRNATarget tool, a total of 67 different candidate target transcripts for the characterized fennel miRNAs were predicted. Additionally, the expression patterns of six selected fennel miRNAs (i.e. fvu-miR156a, fvu-miR162a-3p, fvu-miR166a-3p, fvu-miR167a-5p, fvu-miR171a-3p, and fvu-miR408-3p) were analyzed under salinity stress conditions via qPCR. This article holds notable significance as it identifies not only 40 putative miRNAs in fennel, a non-model plant, but also pioneers the analysis of their expression under salinity stress conditions.